RISK INDICATORS OF TRANSFER PRICING ACCORDING TO THE DOCUMENTS OF INTERNATIONAL ORGANIZATIONS AND WAYS OF THEIR FURTHER USE - KRUGLIAK, VIACHESLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article discusses the issue of establishing a list of transfer pricing risk indicators and determining further ways to use them. The problem of defining and using indicators of transfer pricing risks is relevant and has only recently begun to be discussed by experts in the field of international taxation and in academia. In fact, this category was not study as a separate category of indicators of tax risks, but was only considered in general terms as one of the types of tax risks. The study identified documents from international organizations that consider transfer pricing risks as a separate category of tax risks, as well as an element of tax control over taxpayers' compliance with transfer pricing rules. On the basis of these documents, which summarize the international practice of transfer pricing, an indicative list of transfer pricing risk indicators has been studied and formed and recommendations have been developed on how to further use it by the tax authorities of Ukraine. The definition in this article of an indicative list of transfer pricing risk indicators in accordance with the documents of international organizations is an important prerequisite for understanding further steps to improve the domestic transfer pricing tax control system as a risk-oriented system. The author to suggested to using this list in the future for development and / or creation: a national indicative list of transfer pricing risks indicators and a domestic system for classifying and assessing such risks; standardized processes for identifying and processing information about potential transfer pricing risks and their integration into standardized processes of the general system for processing tax risks in the State Tax Service of Ukraine; determination methods (guidelines) and training materials on this issue; processes for selecting taxpayers for audits and evaluating the results of transfer pricing audits, and the like.
Keywords: transfer pricing; transfer pricing risks; tax risks; tax control; international taxation